The Meaning of Determining Indekos 'Tariffs' from the Indekos Owner's Perspective - INDRIASARI, Rahayu; BAKRY, Moh Iqbal; MAPPARESSA, Nurlaela; PARWATI, Ni Made Suwitri; JURANA, Jurana; DHARMA, Dewa Made Adi (PT Keberlanjutan Strategis Indonesia, 2023)
This research aims to understand and interpret the meaning of